(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Henstock integral is a generalized version of the Riemann integral and in most cases, it is more general than the Lebesgue integral that is not constructed through a measure theoretic standpoint. The PU integral, on one hand, is a Henstock type that utilizes the notion of a partition of unity. In this paper, the Saks-Henstock Lemma and the Change of variable formula for the PU integral will be established.